2018
DOI: 10.5114/ceji.2018.81347
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polyphenols on mast cells with special emphasis on the effect of quercetin and luteolin

Abstract: polyphenols are ubiquitous in food and have long been recognized to possess antioxidant, antiinflammatory and anticancer activities. Mast cells (MCs) are implicated in the pathogenesis of inflammatory diseases, allergy, autoimmunity and cancer. MCs derive from hematopoietic progenitor cells, reside virtually in all vascularized tissue and are activated by crosslinking of fceRi-bound ige (at very high affinity: 1 × 10 10 M-1) with multivalent antigen. MCs in cytoplasmic granules release preformed chemical media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…While we did not specifically examine human mast cells or PDI expression in these cells in this study, it will be important to determine whether PDI has similar effects on IgE-mediated activation in human cells. In this context, interestingly, quercetin and other polyphenols have been shown to modulate human mast cell activity in other studies (51,52).…”
Section: Discussionmentioning
confidence: 88%
“…While we did not specifically examine human mast cells or PDI expression in these cells in this study, it will be important to determine whether PDI has similar effects on IgE-mediated activation in human cells. In this context, interestingly, quercetin and other polyphenols have been shown to modulate human mast cell activity in other studies (51,52).…”
Section: Discussionmentioning
confidence: 88%
“…12,13 As a group, flavonoids tend to exert antioxidative, anti-inflammatory, and neuroprotective properties, but the substitutions can contribute differences in the functional properties. 14,15 Luteolin (3 0 ,4 0 ,5,7-tetrahydroxyflavone) is a common flavone with 2 hydroxylations each on the A and B rings. The presence of the hydroxyl groups at the C3 0 , C4 0 , C5, and C7 positions and the C2-C3 double bond is what structure-activity studies have indicated to be most critical to the bioactivities of luteolin and other flavones.…”
Section: Luteolin: Chemistry and Biochemistrymentioning
confidence: 99%
“…Lut administration through oral route basically diminished the LPO and OH concentration in plasma and colonic mucosa just as it extends the cell strengthening enzymes, which might be a result of the solid cancer prevention agent property of Lut . In an earlier published report, Lut was included as an anti‐inflammatory agent that regulates the inflammatory mediators . The goal of the present examination was to research the defensive impact of Lut against BPA‐incited renal toxicity through suppressing OS, inflammation, and upregulating nuclear factor‐like 2/antioxidant response element/heme oxygenase 1 (Nrf2/ARE/HO‐1) pathway.…”
Section: Introductionmentioning
confidence: 98%